Postoperative neutrophil-lymphocyte ratio predicts unfavorable outcome of acute ischemic stroke patients who achieve complete reperfusion after thrombectomy - Feng, Yao; Bai, Xuesong; Li, Wei; Cao, Wenbo; Xu, Xin; Yu, Fan; Fu, Zhaolin; Tian, Qiuyue; Guo, Xiaofan; Wang, Tao; Sha, Arman; Chen, Yanfei; et al. (Frontiers in Immunology, 2022)
Purpose: Only approximately half of anterior circulation large vessel occlusion (LVO) patients receiving endovascular treatment (EVT) have a favorable outcome. Our aim was to determine the prognostic factors associated with unfavorable outcome following complete reperfusion. Methods: Patients treated with EVT for LVO between January 2019 to December 2021 were prospectively enrolled. Complete reperfusion was defined as modified thrombolysis in cerebral infarction (mTICI) grade 3. A modified Rankin scale at 90 days (mRS90) of 3–6 was defined as unfavorable outcome (i.e., futile reperfusion). A logistic regression analysis was performed with unfavorable outcome as a dependent variable. The receiver operating characteristic (ROC) curve and the area under the curve (AUC) were then used to determine the diagnostic values of these factors. Results: 170 patients with complete reperfusion (mTICI 3) were included in this study. Unfavorable outcome was observed in 70 (41.2%). Higher neutrophil to lymphocyte ratios (NLR) within 24h (p=0.017) and at 3-7d (p=0.008) after EVT were an independent risk factors for unfavorable outcome at 3 months. In addition, older age, higher NIHSS scores, poor collaterals, and general anesthesia were independent predictors of unfavorable outcomes. When accounting for NLR, the diagnostic efficiency improved compared to conventional characteristics. Conclusion: Our findings suggest that advanced age, increased stroke severity, poor collaterals, general anesthesia, and NLR are independent predictors for an unfavorable clinical outcome following complete reperfusion after EVT. Neuroinflammation may merit particular attention in future studies.